3D Cu/In nanocones by morphological and interface engineering design in achieving a high current density for electroreduction of CO2 to syngas under elevated pressure. (July 2022) - Mahyoub, Samah A.; Qaraah, Fahim A.; Yan, Shenglin; Hezam, Abdo; Chen, Chengzhen; Zhong, Juhua; Cheng, Zhenmin
Abstract: Syngas produced electrochemically from carbon dioxide electroreduction is quite appealing. To develop the process on a large scale, it would be essential to use selective and cheap electrodes, and to get high production rate with low energy consumptions. Cu-In catalysts are one of the most intriguing in this context because of their inexpensive cost, high Faradaic efficiency in CO (FECO ), and excellent stability. However, because of the low current densities demonstrated in aqueous electrolytes, productivities have been rather low up to date. This paper shows that the morphological and interface engineering of 3D Cu/In nanocones designed by facile electrodeposition can perform very well for electrochemical carbon dioxide reduction to syngas. Under 1 atm of CO2 pressure and − 0.6 V to − 1.1 V versus RHE, the current density can reach − 20 mA cm −2 with a FE of 100%. Besides, an increase in CO2 pressure as high as 9.5 bars has increased the content of CO2, which enabled CO partial current density (jCO ) to achieve −229.88 mA cm −2, a new record in neutral pH electrolyte for most of the Cu-based electrodes. It proves 3D Cu/In NCs could be the most efficient catalyst for CO2 RR in syngas production to the best of our knowledge. Graphical Abstract: ga1 Highlights: 3D Cu/In NC electrode is prepared through the simplistic electrodeposition technique. The synergistic effects of various factors on CO2 RR have been investigated. Stable activity, syngas selectivity 100%, and high current density were attained. Increasing CO2 partial pressure is helpful for CO2 RR.